2020
DOI: 10.1111/ppc.12491
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between a disposition of gratitude, clinical stress, and clinical satisfaction in nursing students

Abstract: Purpose: This study assessed a disposition of gratitude, and clinical practice stress and satisfaction in nursing students, to determine the relationship between them and provide some basic information towards improving their satisfaction with clinical practice. Design and Methods: This descriptive research was conducted on 171 nursing students from three universities in South Korea using a structured questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
9
0
2
Order By: Relevance
“…Our own study allowed for concluding that students most satisfied with the realization of clinical classes were those students of nursing who perceived a low level of stress. In the study by Moon and Jung (2020), similar conclusions were drawn that people experiencing lower levels of stress were more satisfied with clinical practice [ 47 ].…”
Section: Discussionmentioning
confidence: 80%
“…Our own study allowed for concluding that students most satisfied with the realization of clinical classes were those students of nursing who perceived a low level of stress. In the study by Moon and Jung (2020), similar conclusions were drawn that people experiencing lower levels of stress were more satisfied with clinical practice [ 47 ].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, Zhang (2020) found that across three studies, one of which was time‐lagged by 4 weeks, there was a strong link between trait gratitude and life satisfaction. Trait gratitude is related to satisfaction in other life domains as well, including job satisfaction (Kim et al, 2019; Moon & Jung, 2020) and satisfaction in school (Sun et al, 2014). Trait gratitude is also correlated with compassion satisfaction (Kim et al, 2019), defined as the pleasurable and satisfying feelings that come from helping others, often relevant in healthcare/service contexts.…”
Section: Review Of the Literature Through The Process Model Of Episod...mentioning
confidence: 99%
“…In addition to feeling more satisfied across various domains of life, individuals high in trait gratitude are better able to extract meaning from situations and life as a whole. Trait gratitude is positively related to meaning in life and perceived autonomy (Aghababaei et al, 2018) and negatively related to burnout (Kim et al, 2019; and perceived stress (e.g., Corona et al, 2020;Moon & Jung, 2020;Wood et al, 2007).…”
Section: Cognitive Consequencesmentioning
confidence: 99%
“…30 A recent quantitative study of nursing students reveals a significant relationship between a disposition of gratitude and improved clinical practice satisfaction. 31 Students expressed the theme of finding gratitude through the new opportunities they had despite disappointment. One student wrote, "Although this was not the experience of mentorship that I was hoping for, the pandemic and all that it has brought out in regards to health care has taught me a lot.…”
Section: Finding Gratitudementioning
confidence: 99%
“…Student reflections align with current literature that links satisfaction with clinical experiences with gratitude. 31 For several students, it was clear that their disappointment persisted but was tempered by gratitude: "I understand that we are getting the best experience possible, and I am grateful to have at least that, but it is not equivalent." Students identified specific learning experiences that they were grateful for: "I have had the opportunity to perform leadership roles with my peers in this adapted form of mentorship and I am entirely grateful for the experience it has given me."…”
Section: Finding Gratitudementioning
confidence: 99%